Guidance Note on Information Sharing Between IMF and World Bank Staff. - International Monetary Fund. Strategy, Policy, and Review Department (Washington, D.C. : International Monetary Fund, 2022)
This Guidance Note outlines good practices on information-sharing across key areas in which the Bank and the IMF interact. The note outlines general principles consistent with these frameworks and discusses how the staffs of the two institutions are expected to exchange information related to country operations, technical assistance, and policy work.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Debt Management; Debt; Monetary Policy; Political Economy; Sovereign Debt